Evaluation of major salivary glands with ultrasonography in multiple sclerosis patients - Mustafa Kıranatlı; Melike Yurttaş; Müjgan Güngör; Sibel Canbaz Kabay (BMC, 2024)
Abstract Background This study aimed to investigate the homogeneity of the major salivary glands in multiple sclerosis (MS) patients using ultrasonography (USG), assess DMFT indices, measure resting salivary flow rates, and compare these values with healthy individuals. Methods In this study, 20 individuals diagnosed with Relapsing-Remitting Multiple Sclerosis (RRMS) (mean age 36.15 ± 8.51) and 20 systemically healthy individuals (mean age 35.7 ± 9.22) were included. Oral and radiologic examinations were performed in all individuals. The parotid and submandibular salivary glands were examined using USG, and their homogeneity was assessed based on the scoring system recommended by the Outcome Measures in Rheumatology Clinical Trials (OMERACT) study group. Resting salivary flow rates and DMFT indices were measured, and the obtained data were subjected to statistical analysis. Results The parotid glands exhibited more heterogeneity on USG within the MS patient group than the control group, with a statistically significant difference between the two groups (p = 0.015). A statistically significant correlation was observed in total homogeneity values between the patient and control groups (p = 0.021). Furthermore, the MS patient group exhibited higher DMFT indices and lower salivary flow rates than the control group. The difference between the DMFT indices and salivary flow rate between the patient groups was statistically significant (p = 0.004 and p = 0.002 respectively). Conclusions The parenchyma of the major salivary glands in MS patients exhibited decreased homogeneity than the healthy controls. Additionally, the MS group showed a decrease in salivary flow rate and an increase in the DMFT index. Autonomic dysfunction and medications used for MS are thought to cause salivary gland hypofunction and dry mouth. It can be interpreted that hyposalivation and motor skill losses in MS patients lead to an increase in DMFT index.